TLR2-Deficiency Promotes Prenatal LPS Exposure-Induced Offspring Hyperlipidemia - Cao, Dayan; Wang, Wenjia; Li, Shuhui; Lai, Wenjing; Huang, Xiaoyong; Zhou, Jianzhi; Chen, Xin; Li, Xiaohui (Frontiers in Physiology, 2019)
Toll-like receptor 2 (TLR2), which recognizes several lipopeptides and transduces inflammatory signaling, promotes the pathogenesis of diet-induced dyslipidemia and obesity. TLR2-deficient mice were shown to have improved insulin sensitivity and reduced diet-induced metabolic syndrome. Previous studies demonstrated that prenatal lipopolysaccharide (LPS) exposure causes dyslipidemia accompanied by increased body weight and insulin resistance in offspring. To determine whether TLRs are involved in this complex abnormal phenotype, we analyzed TLR2 and TLR4 expression levels in adipose tissues from offspring with prenatal LPS-exposure (offspring-pLPS) and compared these levels to those of control offspring with prenatal saline-exposure (offspring-pSaline). TLR2 expression was specifically upregulated in the adipose tissue of offspring-pLPS mice. However, unexpectedly, TLR2-deficient offspring-pLPS mice not only presented with an abnormal phenotype comparable to that of wild-type offspring-pLPS mice but also exhibited significantly more severe hyperlipidemia. Our further analyses revealed a dramatic upregulation of TLR4 expression and overactivation of the TLR4/Myd88 signaling pathway in TLR2-deficient offspring-pLPS adipose tissue. Our finding suggests a compensatory genetic interaction between TLR2 and TLR4 in the context of prenatal inflammatory stimulation, and this interaction likely contributes to the prenatal inflammation-induced hyperlipidemia and lipid overload-induced obesity, thus providing a potential mechanism for the fetal origin of adult metabolic diseases.